Faktor-faktor Yang Mempengaruhi Permintaan Wisata di Objek Wisata Pulau Pandang Kab. Batu Bara - Wenda Isnani Mandasari; Yenni Samri Juliati Nst; Atika Atika (-, 2022)
The tourism industry is one of the right means in increasing the economic progress of the community, both locally and globally. Tourism has many impacts and benefits, including in addition to generating foreign exchange and expanding employment opportunities, the tourism sector aims to preserve nature and develop local culture. One type of tourism that is developing in Indonesiais marine tourism. This study aims to determine and analyze ithe influence and magnitude of the influence of the independent variables (services, travel costs, facilities and infrastructure) on the dependent variable (Tourist Demand for Pulau Pandang Tourism Object, Batu Bara Regency) and determine the economic value of Pulau Pandang Tourism Object as a Tourism Object. The method used in this study is a quantitative method by distributing questionnaires or questionnaires to 89 respondents. data processing using SPSS version 22.0. while the type of data required is primary and secondary data. The results showed that the variables of service, travel costs, facilities and infrastructure had a significant positive effect on tourist demand to Pulau Pandang Tourism Object, Kab.Batu Bara. Andhave a positive effect simultaneously.